2012
DOI: 10.1097/mph.0b013e3182427593
|View full text |Cite
|
Sign up to set email alerts
|

FLAG-liposomal Doxorubicin (Myocet) Regimen for Refractory or Relapsed Acute Leukemia Pediatric Patients

Abstract: Despite the success in treating the majority of children with newly diagnosed acute leukemia, children with relapsed or refractory disease are an exceptionally difficult group of patients to cure. We assessed the combination of fludarabine with cytarabine and granulocyte colony-stimulating factor (FLAG) and nonpegylated liposomal doxorubicin (Myocet) in children with either acute lymphoblastic leukemia (ALL) or acute myelogenous leukemia (AML) refractory to first-line therapy or who had relapsed after risk-tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…Pharmacokinetics of free DXR after Myocet ® administration has never been published. Table 2 compares the pharmacokinetic parameters of free DXR observed in this study with parameters of total DXR after 60 mg/m 2 observed in adults which were conventionally measured [26]. Pharmacokinetic parameters of free DXR in our paediatric population were very similar to those observed with conventional DXR in adults.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Pharmacokinetics of free DXR after Myocet ® administration has never been published. Table 2 compares the pharmacokinetic parameters of free DXR observed in this study with parameters of total DXR after 60 mg/m 2 observed in adults which were conventionally measured [26]. Pharmacokinetic parameters of free DXR in our paediatric population were very similar to those observed with conventional DXR in adults.…”
Section: Discussionsupporting
confidence: 58%
“…Considering the advanced disease stage and high level of previous therapy in this population, the efficacy of single-agent Myocet ® should be further explored. To our knowledge, Myocet ® has been used only twice in multi-agent regimen in children [26,27]. In the first study, the combination led to an encouraging remission rate in children with relapsed acute leukaemia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Actually, 29.2% of patients were primary refractory and 17.9% of patients relapsed after HCT. Newly tried drugs in relapsed/refractory AML included gemtuzumab ozogamicin [22,23,24], clofarabine [25], 5-azacytidine [26], decitabine [27], liposomal doxorubicin [28], homoharringtonine [29], plerixafor [30], FLT3 inhibitor [31], ruxolitinib [32], vorinostat [33], and tosedostat [34]. The importance of HCT is also stressed [35,36].…”
Section: Discussionmentioning
confidence: 99%